1991
DOI: 10.1001/jama.1991.03460180070035
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Intravascular Catheter Infection by Antibiotic Bonding

Abstract: We report a prospective, randomized, controlled clinical trial to evaluate the efficacy of antibiotic-bonded catheters in reducing the incidence of intravascular catheter-related infections. Ninety-three central venous catheters and 85 arterial catheters were studied in the surgical intensive care unit. Study catheters were pretreated with the cationic surfactant tridodecylmethylammonium chloride. The anionic antibiotic, cefazolin, was bonded before insertion of the catheters by immersing them in a 50-mg/mL so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(35 citation statements)
references
References 16 publications
0
33
0
1
Order By: Relevance
“…A silver coating showed high antibacterial activity in vitro but was ineffective in vivo; 8,9 antibiotic impregnation reduced bacterial colonization both in vitro and in vivo, but the ideal antibiotic has yet to be found. 7,10 Interesting results were found with the use of triclosan by Chew and associates in vitro, 11 and Desgrandchamps and colleagues 17 reported a study in which hydrogel coatings reduced bacterial adhesion, but found a high degree of encrustation when used in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A silver coating showed high antibacterial activity in vitro but was ineffective in vivo; 8,9 antibiotic impregnation reduced bacterial colonization both in vitro and in vivo, but the ideal antibiotic has yet to be found. 7,10 Interesting results were found with the use of triclosan by Chew and associates in vitro, 11 and Desgrandchamps and colleagues 17 reported a study in which hydrogel coatings reduced bacterial adhesion, but found a high degree of encrustation when used in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…6 Various surface modifications to medical devices have been developed to prevent bacterial adhesion, such as silver-coated surfaces, controlled-release antibiotics, and surface modifications to change hydrophobicity or functional groups having antimicrobial activity. [7][8][9][10][11] Heparin coating was proposed to prevent bacterial adhesion over the last three decades, especially in vascular medicine. [12][13][14] Heparin is an anticoagulant that carries a strong negative electrical charge and helps prevent cell adhesion.…”
Section: Introduction Umentioning
confidence: 99%
“…Ongoing studies are directed toward understanding the mechanism of microbial adsorption and proliferation on material surfaces (13,15,40) and devising new approaches that can be used to avoid this microbial contamination (3,8,9,34). Sequestering the antimicrobial agent close to the device surface has been shown to be an effective approach to reducing the potential for catheter-related infections in patients (18). We believe that the immobilization of the antimicrobial agent by covalent bonding has the advantage of long-term stability and lower toxicity than that by a leach-or a release-based system (10,36).…”
mentioning
confidence: 99%
“…The antimicrobial agents leach out in the course of time and kill microbes or inhibit and prevent the growth of surface attached bacteria [87,88]. A large number of antibiotic agents such as cefzolin [89], minocycline-rifampin [90], teicoplanin [91], silver [92], chlorhexidine-silver sulfadiazine [93], usnic acid, lysostaphin [94], vancomycin [95], gendine [88], gentamicin [96], and so on, have been employed for this purpose.Some of these drug-delivery coatings have already been demonstrated to be effective in preventing infections in vivo. However, among these, only the minocycline-rifampin and chlorhexidine-silver sulfadiazine combinations have been shown to reduce infection rates during short-term use in clinical trials [87].…”
Section: Antimicrobial-releasing Biomaterialsmentioning
confidence: 99%